What’s the Link between Health, Artificial Intelligence, Renewable Energy, Education, and Economic Growth? Glm-Ardl Approaches - Almusallam, Naif; Fikri, Yahya; Nechchad, Abdelhamid; Rhalma, Mohamed (International Journal of Energy Economics and Policy, 2025)
Morocco’s growing rate of solarization is a result of public education programs that have the potential to boost technical innovation and productivity. The current study aims to determine the effects of renewable energy (GGCS), education, artificial intelligence (AI), and health on Morocco’s economic growth. This study combined the ARDL and generalized linear model (GLM) techniques with WDI and ODCE to gather annual data from 1993 to 2023. A long-term relationship between the endogenous and exogenous variables was verified via form replication based on the bound test. However, over time, all of the hypotheses that came from our research were validated. The implications provide light on the complex relationships that exist between Morocco’s economic growth, health, education, artificial intelligence, and renewable energy (GGCS). When creating policies for sustainable development, policymakers should take these links into account, especially when comparing EG to renewable energy (GGCS), artificial intelligence (AI), health, and education. By examining the dynamics of education, AI, health, renewable energy (GGCS), and EG in the Moroccan context for the 1st time, the current study adds to the body of previous knowledge. It challenges a number of accepted beliefs while offering empirical proof of the long-term connections between these variables.